Analysis of Students Reading Literacy Ability in Grade 3 of SDN Cimone 1 Tangerang City - Puspita Sari, Ardita; Nurfadhillah, Septy; Nuraeni, Yeni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to analyze the reading literacy ability of grade 3 students at SDN Cimone 1 Tangerang City. The qualitative descriptive method was used in this study with data collection techniques in the form of interviews, observations, tests, and documentation. The results of the study show that most students have good reading literacy skills, characterized by the ability to recognize letters, read words and sentences, and understand the content of simple reading. Teachers have implemented various strategies to improve students' literacy skills, such as the habit of reading for 30 minutes at the beginning of learning, the use of reading corners, group discussions, and the use of various learning media such as storybooks, magazines, and the internet. However, there are still some students who have difficulty reading fluently and understanding the meaning of the text in depth. This shows the need for an individualized approach and more varied learning to reach all students. Overall, the results of this study reveal that students' reading literacy skills are quite good, but they require improvement and special attention for students with disabilities. This finding is expected to be a reference for the development of reading literacy programs in elementary schools.